2021
DOI: 10.1007/s00392-021-01920-0
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term outcomes after heart transplantation in cardiac sarcoidosis and giant-cell myocarditis: a systematic review and meta-analysis

Abstract: Heart transplantation (HTx) is a valid therapeutic option for end-stage heart failure secondary to cardiac sarcoidosis (CS) or giant-cell myocarditis (GCM). However, post-HTx outcomes in patients with inflammatory cardiomyopathy (ICM) have been poorly investigated. We searched PubMed, Scopus, Science Citation Index, EMBASE, and Google Scholar, screened the gray literature, and contacted experts in the field. We included studies comparing post-HTx survival, acute cellular rejection, and disease recurrence in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 44 publications
(138 reference statements)
0
16
0
Order By: Relevance
“…Bobbio et al showed that heart transplantation has been the only definitive treatment for advanced GCM, and there was no difference in 1-year survival rates after heart transplantation with and without GCM [ 14 ]. In addition, Kandolin et al showed that repetitive endomyocardial biopsies are required for the diagnosis of GCM, and partial clinical remission is shown in 2/3 of patients with immunosuppression [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bobbio et al showed that heart transplantation has been the only definitive treatment for advanced GCM, and there was no difference in 1-year survival rates after heart transplantation with and without GCM [ 14 ]. In addition, Kandolin et al showed that repetitive endomyocardial biopsies are required for the diagnosis of GCM, and partial clinical remission is shown in 2/3 of patients with immunosuppression [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Still, often (25.6%) the definitive diagnosis is made after tissue sampling during implantation of a left ventricular assist device or heart transplantation [ 138 ]. A helpful criterion for choosing to perform a biopsy would be the severity of GCM-caused clinical symptoms, coinciding with two of the main recommendations for performing an EMB in the first place [ 1 , 6 , 139 , 140 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recurrence of sarcoidosis in the transplanted heart has been described and may occur in up to 5% of patients. 47 Long-term outcomes, however, are excellent and appear to be similar or better than in the non-CS population. 47,54…”
Section: Hf Managementmentioning
confidence: 94%
“…46 These findings are supported by the low relapse rate among heart transplant recipients on life-long immunosuppression. 47 On the other hand, long-term immunosuppression is associated with an important burden of side effects, and many patients may experience worse quality of life (QOL) during the treatment itself. 48 We continue immunosuppression for a minimum of 12 months.…”
Section: Diagnostic Criteriamentioning
confidence: 99%